Impact of anaemia on health‐related quality of life and cardiac remodelling in patients with lower risk myelodysplastic syndromes. Results of GlobQoL study. (4th January 2016) - Ramos, F.; Pedro, C.; Tormo, M.; de Paz, R.; Font, P.; Luño, E.; Caballero, M.; Solano, F.; Almagro, M.; Xicoy, B.; Jiménez, M.
Abstract : The aim of this study was to analyse the eventual changes in health‐related quality of life (HRQoL) and left ventricular function (LVF) over a 1‐year follow‐up period in a cohort of patients with lower risk myelodysplastic syndromes (MDS) receiving standard supportive treatment, in order to identify potential clues for early clinical intervention, as well as to analyse how they relate to haemoglobin levels and other aspects of the disease. A total of 39 adult anaemic patients with lower risk MDS were included in a prospective, observational, multi‐centre study. Changes in performance status, functional capacity and HRQoL were collected by using standardised measures (ECOG scale; SPPB, Short Physical Performance Battery; SF‐36, Short‐Form 36 questionnaire; QLQ‐C30, Quality of Life Core Questionnaire; FACT‐An, Functional Assessment of Cancer Therapy‐Anaemia scale questionnaires respectively). Need for transfusion (Linear Analogue Scale Assessment), as perceived independently by the patient and the haematologist, was also recorded. No changes in HRQoL (or LVF) were found, except for slight reductions in SF‐36 physical function ( P = 0.034), SPPB gait speed ( P = 0.038) and FACT‐An score ( P = 0.029), all without apparent immediate clinical relevance for HRQoL, that were unrelated to changes in haemoglobin level. Periodical evaluation of gait speed may assist the clinician in early detection of patient's occult functional decline before it becomes clinically relevant.